Profile portraits of Prince and Princess of Wales - Ghosh, Ayan (2023)
Double portrait of the Prince and Princess of Wales. In the foreground is Alexandra of Denmark (1844–1925) and in the background is Albert Edward (1841–1910), who became Prince of Wales in 1841 and held the title till 1901. The French motto on top, Dieu et mon droit means God and my right, implying the (English) monarch has a God-given (divine) right to rule.